The Impact of Work Environment and Work Discipline on The Performance of Production Section Employees at PT Kaneta Indonesia Karawang District - Desi Purwati; Ayi Muhiban (PT FORMOSA CENDEKIA GLOBAL, 2023)
Work discipline plays a big role in improving employee performance, where a bad work environment will prevent employees from carrying out their duties and responsibilities. This research was conducted on employees of the production department of PT Kaneta Indonesia, Karawang Regency. The aim of this research is to find out how much the work environment and work discipline contribute to the performance, both partially and simultaneously, of employees in the company's production department. Both descriptive and associative research methods are employed, where the part of this research that is part of the analysis are individuals, namely employees in the production department of PT Kaneta Indonesia, Karawang Regency, using a saturated sample where the population chosen as the sample is 105 respondents in the production department. The validity and reliability of the research instruments are tested as part of the analysis method, which also employs multiple linear regression analysis. The results of the study show that performance is partially and simultaneously impactd by exogenous variables (work environment and work discipline) as well as endogenous variables. The impact of the work environment and work discipline on performance is 72%, while 18% is impactd by other variables